Proceedings of the 2003 International Symposium on Low Power Electronics and Design - ISLPED '03 2003
DOI: 10.1145/871506.871561
|View full text |Cite
|
Sign up to set email alerts
|

Reducing power density through activity migration

Abstract: Power dissipation is unevenly distributed in modern microprocessors leading to localized hot spots with significantly greater die temperature than surrounding cooler regions. Excessive junction temperature reduces reliability and can lead to catastrophic failure. We examine the use of activity migration which reduces peak junction temperature by moving computation between multiple replicated units. Using a thermal model that includes the temperature dependence of leakage power, we show that sustainable power d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
188
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 241 publications
(193 citation statements)
references
References 6 publications
3
188
0
Order By: Relevance
“…Due to 3D stack structure, the heat generated by the heat sources must flow through the body of the 3D tiers, and end at the environment interface (ambient) where it is spread through natural convection. Then, the heat flow inside this structure is diffusive in nature and hence, is modeled by its equivalence to an electronic RC circuit [8][9][10]. This is done by first dividing the entire structure into small cubical thermal cells as shown in Figure 2a.…”
Section: D Stack Thermal Modelmentioning
confidence: 99%
“…Due to 3D stack structure, the heat generated by the heat sources must flow through the body of the 3D tiers, and end at the environment interface (ambient) where it is spread through natural convection. Then, the heat flow inside this structure is diffusive in nature and hence, is modeled by its equivalence to an electronic RC circuit [8][9][10]. This is done by first dividing the entire structure into small cubical thermal cells as shown in Figure 2a.…”
Section: D Stack Thermal Modelmentioning
confidence: 99%
“…In the first case the processors can be restructured according to a cluster-based architecture, or by duplicating portions of the processor that are known to be thermal hot-spots. Functional units are duplicated in [9], with increased hardware area and cost: these units are used alternatively to reduce the stress on each single unit (e.g., an ALU or register files). Similar work has been done in [25] in which the only register file has been duplicated, and activity migration is directed toward the spare unit under dynamic thermal constraints.…”
Section: A Design-time Thermal Optimizationmentioning
confidence: 99%
“…Several schemes using architecture adaptation provided DTM solutions [2,5]. Brooks, et al suggested the fetch toggling to avoid thermal limit using the stall of instruction fetching [2].…”
Section: Related Workmentioning
confidence: 99%
“…Brooks, et al suggested the fetch toggling to avoid thermal limit using the stall of instruction fetching [2]. Heo, et al transformed the fetched computation into other duplicated unit during cooling down the overheated unit [5]. However, these schemes cannot satisfy the deadline of workload in real-time.…”
Section: Related Workmentioning
confidence: 99%